Structural and functional characterization of a cold adapted TPM-domain with ATPase/ADPase activity - Cerutti, Maria Laura; Otero, Lisandro Horacio; Smal, Clara; Pellizza, Leonardo; Goldbaum, Fernando Alberto; Klinke, Sebastian; Aran, Martin (Journal of Structural Biology)
The Pfam PF04536 TPM_phosphatase family is a broadly conserved family of domains found across prokaryotes, plants and invertebrates. Despite having a similar protein fold, members of this family have been implicated in diverse cellular processes and found in varied subcellular localizations. Very recently, the biochemical characterization of two evolutionary divergent TPM domains has shown that they are able to hydrolyze phosphate groups from different substrates. However, there are still incorrect functional annotations and uncertain relationships between the structure and function of this family of domains. BA41 is an uncharacterized single-pass transmembrane protein from the Antarctic psychrotolerant bacterium Bizionia argentinensis with a predicted compact extracytoplasmic TPM domain and a C-terminal cytoplasmic low complexity region. To shed light on the structural properties that enable TPM domains to adopt divergent roles, we here accomplish a comprehensive structural and functional characterization of the central TPM domain of BA41 (BA41-TPM). Contrary to its predicted function as a beta-propeller methanol dehydrogenase, light scattering and crystallographic studies showed that BA41-TPM behaves as a globular monomeric protein and adopts a conserved Rossmann fold, typically observed in other TPM domain structures. Although the crystal structure reveals the conservation of residues involved in substrate binding, no putative catalytic or intramolecular metal ions were detected. Most important, however, extensive biochemical studies demonstrated that BA41-TPM has hydrolase activity against ADP, ATP, and other di- and triphosphate nucleotides and shares properties of cold-adapted enzymes. The role of BA41 in extracellular ATP-mediated signaling pathways and its occurrence in environmental and pathogenic microorganisms is discussed. Fil: Cerutti, Maria Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigaciones ...